KOMUNIKASI INTERPERSONAL ISLAM ANTARA PELATIH DENGAN ATLET ANGGAR DI IPASS FENCING CLUB SULAWESI SELATAN (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
This research has the main aim of finding out how Islamic interpersonal communication is between coaches and fencing athletes at the IPASS Fencing Club, South Sulawesi. This research uses a descriptive qualitative type using a case study approach. The data sources are primary data sources and secondary data sources. The data collection methods used were observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion. The research results show that communication between coaches and athletes at IPASS applies to Islamic interpersonal communication. The Islamic interpersonal communication used is Qaulan Sadidan or correct words, Qaulan Maysura or polite words, Qaulan Layyina or gentle communication, Qaulan Karima or noble words, Qaulan Ma'rufa or wise words, and Qaulan Baligha or words with clear meaning. The implications of this research are expected for all athletes and coaches when they want to carry out communication, both verbal and non-verbal, to see and implement effective communication because there are often disturbances, whether environmental, psychological, or other disturbances. This interference causes the message to not be conveyed properly to the communicant. Therefore, during the process of conveying the message, it is necessary to include Islamic communication methods.